A mezőgazdaság átalakulása Közép-Európában és az európai integráció - Fertő, Imre (Tér és Társadalom, 1996)
The most problematic issue for the Central European countries in the integration into the European Union is the integration of agriculture into the system of Common Agricultural Policy. The possibilities for agriculture in the countries of Central Europe are restricted not only be external conditions but also by internal factors. As an effect of the agricultural reforms, the economic environment of agriculture fundamentally changed, as a consequence of which production declined significantly. The unfavourable macro-environment, however, does not justify in itself such a decline in the production of this sector, the reasons are to be found deep in the micro-economic level. The most important reason for the crisis of agriculture in Central Europe is the fact that in this region no agro-business has evolved. The disintegration of the former imperfect co-operation system and the serious consequences of this for production had taken place well before the formation of the new market institutions. These show how one-sided agricultural policies were in the regime. The governments made considerable efforts on the creation of the legal environment of market economy, but they completely forgot about the fact that transaction costs of building out market institutions are so high that it takes a very long time for the actors of economy to accumulate them. In Central Europe, well functioning, effective market institutions, such as a credit system in harmony with the special features of agriculture, stock exchange, wholesale markets, market information services, qualification systems and statistical reports, are either missing or only partially exist. On the other hand, a significant agro-technological development is necessary in these countries, which requires investments in large amounts. In the present situation, however, for lack of capital it seems to be unlikely that the government of any country is able to support researches of this type or spread the results of such researches. In Central Europe the larger proportion of agricultural grants are predatory in character. The rate of productive type agriculturai grants has been very low in the transition so far and is likely to remain at a low level. Another hindering factor is the fact that agricultural producers are only able to a limited extent to adapt themselves to market conditions, they react to different government programmes rather than the signs of the market, thus they are unable many times to utilise favourable market opportunities. Those forecasts which talk about the end of agricultural crisis in the region and the coming years of fast and lasting boom thus seem to be rather optimistic. lt seems to be much more likely that in the medium term we can only expect a moderate growth in the production of the agriculture of Central Europe. Thus the fears that the agricultural potential of the countries of this region may cause problems when joining the European Union, heavily burdening the budget of the Common Agricultural Policy, seem to have weak foundations.